Regional neurochemical profiles in the human brain measured by ¹H MRS at 7 T using local B₁ shimming. - Emir, U; Auerbach, E; Van De Moortele, P; Marjańska, M; Uğurbil, K; Terpstra, M; Tkáč, I; Oz, G (2012)
Increased sensitivity and chemical shift dispersion at ultra-high magnetic fields enable the precise quantification of an extended range of brain metabolites from (1)H MRS. However, all previous neurochemical profiling studies using single-voxel MRS at 7 T have been limited to data acquired from the occipital lobe with half-volume coils. The challenges of (1)H MRS of the human brain at 7 T include short T(2) and complex B(1) distribution that imposes limitations on the maximum achievable B(1) strength. In this study, the feasibility of acquiring and quantifying short-echo (TE =8 ms), single-voxel (1)H MR spectra from multiple brain regions was demonstrated by utilizing a 16-channel transceiver array coil with 16 independent transmit channels, allowing local transmit B(1) (B(1)(+)) shimming. Spectra were acquired from volumes of interest of 1-8 mL in brain regions that are of interest for various neurological disorders: frontal white matter, posterior cingulate, putamen, substantia nigra, pons and cerebellar vermis. Local B(1)(+) shimming substantially increased the transmit efficiency, especially in the peripheral and ventral brain regions. By optimizing a STEAM sequence for utilization with a 16-channel coil, artifact-free spectra were acquired with a small chemical shift displacement error (<5% /ppm/direction) from all regions. The high signal-to-noise ratio enabled the quantification of neurochemical profiles consisting of at least nine metabolites, including γ-aminobutyric acid, glutamate and glutathione, in all brain regions. Significant differences in neurochemical profiles were observed between brain regions. For example, γ-aminobutyric acid levels were highest in the substantia nigra, total creatine was highest in the cerebellar vermis and total choline was highest in the pons, consistent with the known biochemistry of these regions. These findings demonstrate that single-voxel (1)H MRS at ultra-high field can reliably detect region-specific neurochemical patterns in the human brain, and has the potential to objectively detect alterations in neurochemical profiles associated with neurological diseases.